A Few Remarks on the Scope of Judicial Review Performed by the Union Judge - Valančius, Virgilijus (Teisė, 2019)
This article presents some general aspects of the scope of judicial review applied by the Court of Justice of the European Union as well as its particularities in competition (the research comprises cases concerning agreements restricting competition and the abuse of a dominant position) and civil service cases. As legal texts of the European Union do not provide the precise scope of judicial control, the jurisprudence of the Court of Justice of the European Union is one of the main sources giving clarifications on this issue. This article focuses accordingly on the presentation of the relevant jurisprudence, which analyzes the subject matter in general and reflects the evolution of this Court’s approach in the said competition and civil service cases.